Disease Dadru: A Historical Review - Saini, Jeeta Ram; Mandal, Sisir Kumar; Sharma, Madan Mohan (International Research Journal of Ayurveda & Yoga, 2020)
In Āyurveda all the skin disease considered in Kuṣṭha. Which are further categorized in to Mahākuṣṭha and Kṣudrakuṣṭha. Kuṣṭha is produced invariably by the vitiation of the seven factors i.e. 3 Doṣā and 4 Dūṣyā.i When the vitiated Doṣā provoke the four body elements and if this derangement of seven Dravyā is not cared to, a disease is formed inside the body which manifests itself on outermost part of the body. Skin is mostly affected by fungus as it is external covering of body. In Āyurveda Tinea infection is termed as Dadru. Ācārya Caraka considered Dadru in Kṣudra Kuṣṭha and Doṣa dominance is Kaphapitta. Ācārya Suśruta considered Dadru in Mahā Kuṣṭha and Doṣa dominance is Kapha. Dadru is a type of Kushta roga, which is characterized by the cardinal symptoms like Kaṇḍu, Utsannamaṇḍala, Rāga and Piḍikā and the lesions resembling the skin of a tortoise. History of any science is a cluster of facts and it helps to provide the guidelines about our present and future path. So profound knowledge of the historical events can help us to correlate between today and ancient axioms or Āyurveda texts and modern medicinal texts with the help of scientific parameters. The history of Indian medicine starts from Veda, so the history of Dadru Roga beginning from Vedā.